2020
DOI: 10.3389/fpsyg.2020.00479
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Experiments on Emotional Face Recognition Find No Evidence of Mood-Congruent Effects

Abstract: Mood-congruent effects have been demonstrated many times, but few studies have managed to replicate the effect with natural moods. Additionally, the ecological validity of mood induction and real-time observation deficiency remain unresolved. Using a newly developed, virtual-reality-based eye-tracking technique, the present study conducted real-time observations of mood effects on emotional face recognition with simulated "real-life" pleasant and grisly scenes. In experiment 1, participants performed an emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Yet, these two experiments from Hartig et al (1999) attempted to induce mood with environmental manipulations (i.e., placing participants in urban or natural settings) that produced only minor (Experiment 1) or no differences (Experiment 3) in reported affect. In a similar vein, Zhong et al (2020) used virtual reality to construct pleasant or unpleasant (grisly) environments, which elicited slight shifts in valence ratings compared to neutral environments, but this induction method was also unable to produce subsequent MCM. The experiments from Liu et al (2008), Nielson and Lorber (2009), and Wang and Ren (2017) additionally failed to show MCM.…”
Section: Encoding-retrieval Assessmentsmentioning
confidence: 99%
“…Yet, these two experiments from Hartig et al (1999) attempted to induce mood with environmental manipulations (i.e., placing participants in urban or natural settings) that produced only minor (Experiment 1) or no differences (Experiment 3) in reported affect. In a similar vein, Zhong et al (2020) used virtual reality to construct pleasant or unpleasant (grisly) environments, which elicited slight shifts in valence ratings compared to neutral environments, but this induction method was also unable to produce subsequent MCM. The experiments from Liu et al (2008), Nielson and Lorber (2009), and Wang and Ren (2017) additionally failed to show MCM.…”
Section: Encoding-retrieval Assessmentsmentioning
confidence: 99%
“…Research using implicit measures has shown that 3D VR has the potential to elicit emotions, opening new opportunities to the scientific community 36 . In addition, eye-tracking methodologies make it possible to observe in real time how an individual explores the scene presented 26 , 37 . Although this paper does not compare IVR with classical photo and video stimuli in facial emotion recognition, it is a truism that the use of dynamic avatars for emotion recognition tasks has become widespread in the last 20 years 38 41 .…”
Section: Introductionmentioning
confidence: 99%